Interstitial pneumonitis following intrapleural chemotherapy - Zappa, Luis (BioMed Central, 2009)
BACKGROUND: Mucinous neoplasms within the abdomen may disseminate by direct extension through the diaphragm to involve the pleural space. Treatment of this condition is by parietal and visceral pleurectomy followed by hyperthermic intrapleural chemotherapy. CASE PRESENTATION: In this case report a patient developed persistent right upper lobe interstitial pneumonitis and progressive parenchymal fibrosis following intrapleural chemotherapy treatment with mitomycin C and doxrubicin. The condition persisted until death 28 months later. Death was from progressive intraabdominal disease with intestinal obstruction and sepsis associated with progressive pulmonary parenchymal disease. The right pleural space disease did not recur. CONCLUSION: This manuscript is the first case report describing interstitial pneumonitis and lung fibrosis following intrapleural chemotherapy. Since pulmonary toxicity from chemotherapy is a dose-dependent phenomenon, dose reduction of intrapleural as compared to intraperitoneal hyperthermic chemotherapy may be necessary.